Acceptance and commitment therapy guided self-help for psychogenic non-epileptic seizures - Barrett-Naylor, Ruth (2017)
Psychogenic non-epileptic seizures (PNES) are a relatively common condition, however, seizures can be debilitating for patients and are associated with high levels of psychological distress, reduced quality of life and reduced functionality. Despite the debilitating effects of the condition, there is thus far no recommended treatment. Although psychological therapy is often sought following the diagnosis of PNES, there remains relatively little research in the area comparing treatment efficacy. Nevertheless, many treatment efficacy studies focus on the application of cognitive behavioural therapy to PNES and the results produced so far appear promising, however, the psychotherapeutic mechanisms of change for such therapies are less clear.